Designing standard plagiarism guidelines for internet based material - Ali, Zuraina; Kassim, Hafizoah; Mohd Ali, Zarina; Mohd Radzuan, Noor Raha; Khamis, Nor Yazi (2008)
With the widespread use of the Internet especially in higher education institutions, plagiarism among students needs careful deliberation and action. Although plagiarism is common among students, it is only fair to investigate whether they clearly understand its definitions and the consequences of committing plagiarism before any form of penalty is to be imposed. Hence, the aim ofthis study is two-fold: to investigate the level of understanding and awareness of Universiti Malaysia Pahang (UMP) students and lecturers on plagiarism, and to examine the nature and extent of plagiarism, if evident, in students' final year project, projek sarjana muda (PSM) research reports. Two sets of questionnaires developed by researchers, PLaQ-s and PLaQ-1, were administered separately in the student survey and academic staff online survey respectively. 1 0 copies of students' P SM reports from one faculty were then randomly collected and the literature review sections of students' PSM reports were later analysed as this section could contain more elements of plagiarised texts compared to other sections. Plagiarism analysis framework (P AF) was developed by researchers for use in manual analysis while the Web-based plagiarism detection engine Plagiarism-Finder l.Ou) available for free, was also used in electronic analysis. The findings in this study showed that although plagiarism was evident in selected sample of UMP students' PSM reports, free digital plagiarism detection tool was not solely capable on its own of performing thorough analysis and this had to be followed by manual mode of detection using PAF. It was concluded that despite the existence of awareness and general understanding of what plagiarism was, selected sample of students' PSM did contain both textual and non-textual form of plagiarism, from minor to plagiarism outright, calling for serious proactive and reactive actions from university lecturers, administrators and policy makers.